The quality of roselle (Hibiscus sabdariffa L.) juices made from roselle calyces stored at different cold temperatures - Ibrahim, R.; Mazuki, N.A.F. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Roselle (Hibiscus sabdariffa L.) from the family of Malvaceae is normally referred to the calyces which have brilliant red color and unique flavor that makes it a valuable food product commonly used to make preserves, jams and beverages. This study was conducted to determine the physico-chemical characteristics and sensory acceptability of rosellejuices made from roselle calyces stored at different cold storage temperatures; 5±1°C, -19±1°C, -80±2°C for 7 days and fresh roselle was used as control. The physico-chemical characteristics studied were colour, total soluble solids, titratable acidity, ascorbic acid and anthocyanins contents. The sensory evaluation was also carried out which involved the acceptability test on the attributes of colour, aroma, taste (sweetness and sourness) and overall acceptability. Roselle juicesmade from frozen roselles (-19±1°C and -80±2°C) showed significantly higher L* values followed by roselles stored at 5±1°C and fresh roselles. In addition, juice made from fresh roselle had significantly the highest a*, b* values and anthocyanins content followed by roselle stored at 5±1°C and -80±2°C where juice made from roselle stored at -19±1°C showed the lowest values. However, for ascorbic acid content, fresh roselle also showed the highest value followed by roselle stored at -80±2°C, -19±1°C and the lowest was roselle stored at 5±1°C. The sensory evaluation showed that, roselle juice made from fresh calyces was the most acceptable in almost all the attributes compared to chilled and frozen roselles. In conclusion, juice made from fresh roselle had almost all the preferred physico-chemical qualities and sensory acceptability as compared to the chilled and frozen roselles.